Change in the occurrence of common vascular plants in Finland between 1960–2000 and 2001–2019 - Lahti, Tapani; Lampinen, Raino (Articles, 2021)
Data from a national vascular plant atlas, containing species occurrence data from 1-km squares in different parts of Finland over a period of 60 years, were used for detecting change in the commonness of 712 species. The dataset was divided into two parts, one containing squares inventoried between 1960 and 2000 (Period A, 4 596 squares) and the other containing squares from 2001 to 2019 (Period B, 3 692 squares). Of the 712 species analysed, we observed 124 species that showed consistent increase in commonness from Period A to Period B. Only eight species showing a decline from Period A to Period B were found. Our results indicate that human activities have been the main driving force behind the floristic change in Finland during the study period. The successful competitors are mostly alien and apophytic native species that are able to utilize habitats modified by cultural influence.